Therapeutic evaluation of a traditional Sri Lankan herbal oil in the management of diabetic foot ulcers: An observational study - Rasangika, K.W.; Jayawardhane, N.D.N. (University of Colombo, 2025)
Diabetic foot ulcers represent a significant clinical challenge, frequently leading to infection, prolonged hospitalization, and potential limb amputation. Despite advancements in conventional medical therapies, chronic non-healing ulcers remain prevalent, necessitating alternative or complementary treatment approaches. This preliminary observational study evaluates the efficacy of a traditional Sri Lankan medicinal oil, as documented in the Thalpathe Piliyam (Volume 16), in promoting wound healing among Diabetic foot ulcers patients. Two patients diagnosed with lower limb ulcers of grades I and II were selected based on predefined inclusion and exclusion criteria. Eligible participants were aged 18–70 years, diagnosed with type 2 diabetes mellitus, and presenting with Diabetic foot ulcers which is not chronic more than six months. Patients with malignant or Aramana wounds or those suffering from hypertension, dyslipidemia or other major systemic disorders, were excluded. Following the wound cleansing with saline and Panchavalkala kashaya, the traditional oil was applied topically once daily over 9 to 28 days. Clinical outcomes were evaluated using a Visual Analogue Scale, assessing pain, exudate characteristics, odor, ulcer edge characteristics, and floor granulation. Informed written consent was obtained from both participants. Case 1 achieved complete healing within 9 days; Case 2 exhibited over 75% improvement in wound parameters by day 28. Phytochemical analysis of the oil revealed the presence of tannins, flavonoids, and alkaloids, which exhibit known anti-inflammatory, antimicrobial, and wound healing properties. These preliminary findings suggest that the traditional oil holds therapeutic potential for Diabetic foot ulcers treatment. Further controlled clinical studies are recommended to confirm its efficacy and safety profile for broader clinical application.
Keywords: Diabetic foot ulcers; Traditional medicine; Madhumehajanya vrana; Herbal oil; Wound healing